Aplicação da espectrometria de raios gama na caracterização de cerâmicas arqueológicas - Rodriguez, Duvan Gil (2020)
Gamma ray spectrometry or GRS is a nuclear analytical technique that has not been commonly used in archaeometry. In most applications of this technique, it is important to control the measurement geometry, which is less trivial to achieve with archaeological samples, where preserving the integrity of the sample is important. Despite the need for geometry control, the technique employed without strict control can reveal some interesting characteristics of the samples, especially when analyzing the ratios of the liquid areas between different peaks of the spectrum, a procedure that reduces the influence of geometry on the result of the measure. The main objective of this work was to contribute with the insertion of the gamma ray spectrometry technique as a useful tool in the archaeometry service. In this work, two procedures were tested in order to estimate the ratios of elementary concentrations eTh/% K, eTh/eU and % K/eU in ceramic samples without strict control of the measurement geometry. Method 1 follows the standard procedure suggested by the IAEA to measure elementary concentrations and method 2 uses the ratios of the net peak areas, corresponding to gamma rays emitted by nuclides of the same radioactive series present in the sample, to calculate a geometric correction factor for the estimation of elementary concentration ratios. The methods were tested by analyzing samples of ceramic vase for commercial use. The absolute ratio results for samples of diverse geometry are consistent with the results obtained for samples with geometry control at a level of statistical significance of 95%. The developed methodology was applied to samples of archaeological ceramics from three archaeological sites in the state of Maranhão, Brazil. According to the results of the study, it is possible to characterize archaeological ceramics using the low-resolution gamma ray spectrometry technique, respecting the integrity of the artifacts, a very important consideration for archaeologists, archaeologists and curators of museums and cultural heritage sites.